Non-adiabatic Quantum Dynamics of the Dissociative Charge Transfer He++H2 → He+H+H+ - De Fazio, Dario; Aguado, Alfredo; Petrongolo, Carlo (Frontiers in Chemistry, 2019)
We present the nonadiabatic, conical-intersection quantum dynamics of the title collision where reactants and products are in the ground electronic states. Initial-state-resolved reaction probabilities, total integral cross sections (ICSs), and rate constants of two vibrational states (v0=0 and 1), of H2 in the ground rotational state (j0=0) are obtained at collision energies Ecoll≤3 eV. We employ the lowest two excited diabatic electronic states of HeH , a coupled-channel time-dependent real wavepacket method, and a flux analysis. Both probabilities and ICSs present a few groups of resonances at low Ecoll, due to an ion-induced dipole minimum in the entrance channel, and whose amplitudes decrease with the energy. At higher Ecoll, reaction probabilities and cross sections increase monotonically up to 3 eV, remaining however quite small. When H2 is in the v0=1 state, the reactivity increases by ~two orders of magnitude at the lowest energies and by ~one order at the highest ones. Initial-state resolved rate constants at room temperature are equal to 1.74x10–14 and to 1.98 x10–12 cm3s–1 at v0=0 and 1, respectively. Test calculations for H2 at j0=1 show that the probabilities can be enhanced by a factor of ~1/3, that is ortho-H2 seems ~4 times more reactive than para-H2.